Values Attached to Educational Goals, Study Processes, and Educational Motivation (Journal of Education and Development, 2017)
This study examines the relationship between educational values and educational goals, student motivation and study processes, and how values attached to educational goals predict motivation and student study processes. 181 randomly selected graduate and undergraduate students from a Midwestern university in the United States were recruited to participate in an online survey. The results demonstrated that values attached to educational goals and perceived educational outcomes have a weak but significant positive correlation with student study processes. In addition, values for educational goals significantly predict student study processes and educational motivation. Thus, it is suggested that educators should enhance personal values for education and develop strategies aimed at building and enhancing students’ values for education. Further studies on the values for educational goals and perceived educational outcomes will contribute to the understanding of concepts and theories related to motivation in education and possibly influence student outcomes, such as dropout rates. Teachers and people working in higher education need to understand that students’ values of perceived outcomes and goals are relevant components to their motivation in education. Because there are few studies on students’ values for educational goals and outcomes, more empirical evidence is imperative to help teachers assist students sustain their motivation in their educational pursuit and improve their study processes.